2001
DOI: 10.1023/a:1011510923900
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This bulletin describes state-of-the-art universal and selective prevention programs designed to promote parent and teacher competencies and to prevent conduct problems. In addition, it describes indicated interventions designed for children who already have been diagnosed with oppositional defiant disorder and/or conduct disorder. Emphasis is placed on empirically supported programs that have identified key malleable risk factors in children, families, and schools, which have been shown in longitudinal resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(103 citation statements)
references
References 53 publications
5
93
0
5
Order By: Relevance
“…Traditionally, earlier studies have highlighted aspects such as the family's socioeconomic status as a risk factor for the development of conduct problems (e.g. Webster-Stratton & Taylor, 2001). Specifically, poverty has been associated with a significant increase in the likelihood of behavioral alterations in the children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, earlier studies have highlighted aspects such as the family's socioeconomic status as a risk factor for the development of conduct problems (e.g. Webster-Stratton & Taylor, 2001). Specifically, poverty has been associated with a significant increase in the likelihood of behavioral alterations in the children.…”
Section: Discussionmentioning
confidence: 99%
“…One such risk factor mentioned repeatedly in specialized studies is parenting practices, in the widest sense of the term (Webster-Stratton & Taylor, 2001). Accordingly, in recent years researchers have stressed the importance of studying the behavior of the parents in relation to their children, and the manner in which the children develop from both a socioemotional and a behavioral point of view (Hardaway, Wilson, Shaw, & Dishion, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis showed substance abuse with or without co-occurring disorders placed juveniles at greater risk for offense escalation, a finding consistent with other studies on recidivism Schubert, Mulvey, Glasheen, 2011). Webster-Stratton andTaylor (2001) found that substance abuse in juveniles often exists simultaneously with CD, undesirable behaviors, and delinquency. Therefore, it is important for children/youth with mental health issues who encounter the juvenile justice system to receive screening for substance abuse and, if needed, referral for treatment (Welch-Brewer et al, 2011).…”
Section: Prevalence Rates Of Mental Health Issues In the Juvenile Jusmentioning
confidence: 99%
“…High-quality early childhood interventions can serve as an antecedent for children's later academic development (Maier, Vitiello, & Greenfield, 2012;Duncan et al, 2007;DiPerna, Volpe, & Elliot, 2005;Rimm-Kaufman, Pianta, & Cox, 2000;Shonkoff & Phillips, 2000). Given the importance of early academic success, numerous interventions focus on children's early development (Furlong, McGilloway, Bywater, Hutchings, Smith, & Donnelly, 2012;Fuchs, Fuchs, Thompson, Otaiba, Yen, McMaster, Svenson, & Yang, 2001;Webster-Stratton & Taylor, 2001;Domitrovich & Greenberg, 2000). A growing body of research finds temperament-based interventions instrumental in children's social, emotional, and academic development (Collins, O'Connor, McClowry, in progress, McClowry & Collins, 2012).…”
Section: Introductionmentioning
confidence: 99%